The Best American Short Stories, 2006 - Patchett, Ann.; Kenison, Katrina (Boston : Houghton Mifflin, 2006)
Since 1915 the Best American series is the premier annual showcase for the country's finest short fiction and nonfiction. Each volume's series editor selects notable works from hundreds of periodicals. A special guest editor, a leading writer in the field, then chooses the best twenty or so pieces to publish. This unique system has made the Best American series the most respected, and most popular, of its kind.
Introduction / Ann Patchett -- Once the shore / Paul Yoon -- Awaiting orders / Tobias Wolff -- The ambush / Donna Tartt -- Secret / Maxine Swann -- Dominion / Mark Slouka -- So much for Artemis / Patrick Ryan -- Refresh, refresh / Benjamin Percy -- Self-reliance / Edith Pearlman -- The view from Castle Rock / Alice Munro -- Tattooizm / Kevin Moffett -- Cowboy / Thomas McGuane -- The dog / Jack Livings -- After a life / Yiyun Li -- The conductor / Aleksandar Hemon -- Today I'm yours / Mary Gaitskill -- How we avenged the Blums / Nathan Englander -- Grandmother's nose / Robert Coover -- A new gravestone for an old grave / David Bezmozgis -- The casual car pool / Katherine Bell -- Mr. Nobody at all / Anne Beattie with Harry Mathews.
Keywords: Short stories, American; Short stories, Canadian; American fiction -- 21st century; Canadian fiction -- 21st century